Considerations in cultural adaptation of parent–child interventions for African American mothers and children exposed to intimate partner violence - Cervantes, Breana R.; Allman, Madeleine; Walton, Quenette L.; Jouriles, Ernest N.; Sharp, Carla (Frontiers in Psychology, 2024)
African American women are at disproportionate risk of experiencing intimate partner violence (IPV) and consistently report more severe and recurrent IPV victimization in comparison to their White and Hispanic counterparts. IPV is more likely to occur in families with children than in couples without children. Parenting in the wake of IPV is a challenging reality faced by many African American women in the United States. Despite the urgent need to support mothers who have survived IPV, there is currently no culturally adapted parenting intervention for African American mothers following exposure to IPV. The aim of this review is to summarize and integrate two disparate literatures, hitherto unintegrated; namely the literature base on parenting interventions for women and children exposed to IPV and the literature base on parenting interventions through the lens of African American racial and cultural factors. Our review identified 7 questions that researchers may consider in adapting IPV parenting interventions for African American women and children. These questions are discussed as a possible roadmap for the adaptation of more culturally sensitive IPV parenting programs.